On the Heterostegina– Tansinhokella– Spiroclypeus Lineage(s) in SE Asia - Peter Lunt; Willem Renema (Ikatan Ahli Geologi Indonesia, 2014)
The evolutionary series from Heterostegina (Vlerkina), through Tansinhokella to Spiroclypeus is reviewed. Both previously unpublished work (Muhar, 1956) and new field data is used to support the hypothesis that this evolutionary development can be observed twice in the fossil record. The first lineage became extinct at the Oligocene- Eocene boundary, and then the same morphologies re-appeared in the middle and later Oligocene. Both the negative evidence (absence) of Early Oligocene [Tc / Td Letter Stage] records, and the positive evidence of a gradual evolutionary series in Oligocene times, are discussed. At the moment there is no reliable way to distinguish the Late Eocene and later Oligocene tests, so the same generic name has to be applied to each occurrence, even though they are separated in time. This leads to the unusual situation that all three genera have to be reported as having two evolution and two extinction datums.The later Oligocene transition of Tansinhokella into Spiroclypeus is observed to be more gradual than the morphological criteria used to separate these genera in 1991 (Banner and Hodgkinson), but the two names are retained for end members of a gradual series with a distinct stratigraphic record.The hypothesis of iterative evolution was based on work in Java, and it was predicted that the other areas in Asia would preserve the same evolutionary pattern in the stratigraphic record. This work shows that the second evolutionary development of Tansinhokella and Spiroclypeus was at the same time in three geographically separate areas, the most reasonable explanation for which is iterative evolution, rather than ecophenotypic fluctuations or faunal migrations.The importance of Tansinhokella in the biostratigraphic subdivision of Letter Stage Te is highlighted.